Hegel’s philosophy of religion - ماشي نور; جلال بدلة (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This research aims to introduce the important position occupied by the philosophy of religion within the Hegelian system, given that religion, according to Hegel, is the manifestation of the absolute idea, the absolute spirit; That is, God appears in history in an inevitable way, and that spirit must be positioned and take its place, but that movement does not come all at once, but rather in stages, and is presented according to a rational and logical sequence until we reach the realization of the absolute spirit in a final and complete manner. Hegel divided the stages of the development of religion It is divided into three sections: the religion of nature, in which thought appeared concretely in reality, and the religion of spirituality, which represented the rise of reality and its rise to thought, leading to absolute religion, in which thought is united with reality, which is considered the pinnacle that the human mind reaches and represents the return of the comprehensive idea to itself, which was embodied. In the Christian religion, which brought together the divine nature and the human nature, which was embodied in the person of Christ. The concept of religion according to Hegel refers to the spirit’s awareness of itself, meaning it is the idea. Its subject is God, who only appears in thought because God is the idea for Hegel, and it is not possible to reach his knowledge without using pure reason to achieve absolute knowledge. He worked to transform the content of religion into thought. , and then turn it into reality; According to Hegel, God turned into what is called the Absolute, Christ into incarnation, and the Trinity into controversy. Religion turned into ideas and controversy. According to Hegel, man realizes himself in religion. The soul realizes itself, gets rid of everything that exhausts its powers, achieves complete satisfaction and eternal salvation from everything attached to it of finitude, and realizes the infinite, the unlimited, which is the highest thing a person can reach, and this awareness of the infinite, the unlimited, that is, God, is the true religion according to the Hegelian vision. The ultimate goal of Hegelian theology, which reached the peak of its development, was manifested in the humanization of God. That is, in the sense of likening God to man, which was embodied in the idea of ​​Christ. Then the mind comes to show that this idea is a product of the soul, and the soul, according to Hegel, is the human soul. Through this, it becomes clear that man knows himself in the person of Christ and maintains himself within thought as an entity that exists for the sake of same.